Who are the outsiders and what do they want? Welfare state preferences in dualized societies - Häusermann, Silja; Schwander, Hanna (Paris, 2011)
"This paper makes three contributions. First, it presents a new conceptualization and measurement of outsider-status, which is based on social class and which takes into account that the category of outsiders is composed differently in different countries, depending on labor markets and welfare states. Second, it argues theoretically and shows empirically that the classbased measure of insider-and outsider status has a stronger explanatory power with regard to individual-level welfare preferences than the measure based on labor market status. And third, it demonstrates empirically that dualization, combined with skill-levels, shapes people’s preferences with regard to different welfare policies: Outsiders have stronger preferences for redistribution and for social investment than insiders. The analyses are based on micro-level ISSP data."